International space security of the third decade of the twenty-first century (selected aspects) - Delong, Marek; Dworzecki , Jacek; Szkurłat, Izabela; Żebrowski , Andrzej (Polityka i Społeczeństwo, 2023)
The beginning of the 21st century saw many complex phenomena, events and processes with diverse backgrounds shaping the new order related to international security after the breakdown of the bipolar division of the world. Despite the ongoing euphoria, the time of transition has been a string of military and non-military conflicts, whose participants have fought for dominance in the international security environment and for leadership in the global security space. The three main actors: The United States, China and Russia are pursuing their partisan goal, which is dominion in the global security space. The U.S. policy, which is aimed at confrontation, both with Russia and China is noteworthy. This conflict is present in the political, economic, military and scientific-technical spheres, as in the cases of China, which is a leader in access to artificial intelligence. The world is watching the Russia-Ukraine armed conflict. Each side has opponents and supporters. The conflict is affecting international political, economic and military relations. This complex and unpredictable situation is accompanied by a global information war, with participants pointing to their particular political goals. The global security space is evolving, but will politicians be able to make rational decisions so as not to cross the tipping point?"